Future mobile networks 3G and beyond - Clapton, Alan (London, United Kingdom Institution of Engineering and Technology, 2001)
This book explores the future of mobile communication networks from 3G trials, developments and products, to what will follow in the future. The increasing demand for services and higher quality continue to drive forward the technological capabilities. The implications of increasing mobile consumer numbers on a global scale are investigated, as well as the convergence of mobile and the Internet , which it is envisaged, will provide the next massive growth burst to the mobile market and 3G networks. The book covers the evolution to support multimedia architecture from GSM to UMTS, voice and Internet multimedia in UMTS networks, 3G service control, the open systems access (OSA) application programming interface (API) issue, and mobile standards which are a critical dependency for 3G and future developments. The book also explores the virtual university research initiative on mobility, virtual centre of excellence in mobile and personal communications, and BT Wireless' other mobile venture and alliances in the mobile arena. This book is essential reading for telecommunications engineers and managers, researchers and post graduate students in communications who need to understand the expanding market expectations and the technological solutions available in this dynamic field.
Electronic reproduction.
Keywords: Wireless communication systems; Mobile communication systems; Electronic books